The Effect of English Teacher Creativity on Student Participation in Differentiated Learning - Tia Rahmatika (STKIP Taman Siswa Bima, 2025)
This research investigates the impact of teacher creativity on student participation in differentiated learning at SMPN 39 Samarinda, involving 43 students. Using a quantitative approach, the research employed regression analysis to examine the relationship between teacher creativity and student participation. The findings revealed a significant positive correlation, with teacher creativity explaining 31.9% of the variation in student participation. The ANOVA test confirmed the statistical validity of the regression model, with a significance value of 0.000, indicating that teacher creativity plays a crucial role in enhancing student engagement. These results suggest that when teachers apply creative teaching methods and adapt their instruction to the diverse needs of students, it leads to greater student involvement. This research highlights the importance of fostering creativity in teaching practices to improve student participation, and emphasizes the need for educational institutions to support teachers in developing their creative skills.